2013
DOI: 10.1159/000350671
|View full text |Cite
|
Sign up to set email alerts
|

Stress Management and Mind-Body Medicine: A Randomized Controlled Longitudinal Evaluation of Students' Health and Effects of a Behavioral Group Intervention at a Middle-Size German University (SM-MESH)

Abstract: Background: Student life can be stressful. Hence, we started a regular mind-body medical stress management program in 2006. By today, more than 500 students took part and evaluations showed significant results, especially with regard to a reduction of stress warning signals. For further analysis, we now decided to run a randomized controlled longitudinal trial. Methods: Participating students at Coburg University were randomized into an intervention (n = 24) or a waitlist control group (n = 19). The interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…The rating follows a 10-point system (0 = does not stress me at all, 10 = stresses me a lot). The scale was developed and validated by Esch et al [23, 24]. Example items for vegetative-endocrinological symptoms are “rapid heartbeat,” “chest tightness,” or “excessive sweating.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rating follows a 10-point system (0 = does not stress me at all, 10 = stresses me a lot). The scale was developed and validated by Esch et al [23, 24]. Example items for vegetative-endocrinological symptoms are “rapid heartbeat,” “chest tightness,” or “excessive sweating.”…”
Section: Methodsmentioning
confidence: 99%
“…A pilot study showed internal consistency and a moderately high reliability and validity [27]. We used a German version of this questionnaire (FS-D) translated by Esch et al [23, 24]. Example items are “I lead a purposeful and meaningful life” and “I am engaged and interested in my daily activities.”…”
Section: Methodsmentioning
confidence: 99%
“…Here, scholars use multidimensional scales to evaluate how well individuals see themselves functioning as they strive to achieve sufficient levels of purpose, contribution, integration, autonomy, intimacy, acceptance, and mastery in life. Further, positive psychology and stress management approaches, such as MBM, may use these measures on stress and the outcome of interventions for behavior change and stress resilience training [34,35,36], or they may use integral, i.e. short-form flourishing scales [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they had some prior exposure to both types of relaxation inductions utilized in this study. They had been introduced to the theory of mind-body techniques and also participated in an 8-week mind-body related stress-reduction program in the foregoing semester, which has been described and evaluated elsewhere [25,26]. The current study was conducted at the end of the fourth semester, after the students had been introduced to different forms of relaxation techniques including mindfulness meditation, walking meditation, fantasy journey, as well as yoga, progressive muscle relaxation, and autogenic training under the supervision of two mind-body experts for the whole semester (NK and TE).…”
Section: Methodsmentioning
confidence: 99%